Patellar Tendon Strain Associates to Tendon Structural Abnormalities in Adolescent Athletes - Mersmann, Falk; Pentidis, Nikolaos; Tsai, Meng-Shiuan; Schroll, Arno; Arampatzis, Adamantios (Frontiers in Physiology, 2019)
High mechanical strain is thought to be one of the main factors for the risk of tendon injury, as it determines the mechanical demand placed upon the tendon by the working muscle. The present study investigates the association of tendon mechanical properties including force, stress and strain, and measures of tendon micromorphology and neovascularization, which are thought to be indicative of tendinopathy in an adolescent high-risk group for overuse injury. In 16 adolescent elite basketball athletes (14-15 years of age) we determined the mechanical properties of the patellar tendon based by combining inverse dynamics with magnetic resonance and ultrasound imaging. Tendon micromorphology was determined based on a spatial frequency analysis of sagittal plane ultrasound images and neovascularization was quantified as color Doppler area. There was a significant inverse relationship between tendon strain and peak spatial frequency (PSF) in the proximal tendon region (r = −0.652, p = 0.006), indicating locally disorganized collagen fascicles in tendons that are subjected to high strain. No such associations were present at the distal tendon site and no significant correlations were observed between tendon force or stress and tendon PSF as well as between tendon loading and vascularity. Our results suggest that high levels of tendon strain might associate to a micromorphological deterioration of the collagenous network in the proximal patellar tendon, which is also the most frequent site affected by tendinopathy. Neovascularization of the tendon on the other hand seems not to be directly related to tendon loading and might be a physiological response to a high frequency of training in this group. Those findings have important implications for our understanding of the etiology of tendinopathy and for the development of diagnostical tools for the assessment of injury risk.